Investigation of acoustic wavelength effects on silicon compatible Al doped ZnO SAW resonator - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin (IEEE, 2016)
This paper addresses the investigation of acoustic wavelength effects on silicon compatible SAW resonator based on Al doped ZnO thin film. Three different resonators at acoustic wavelength of 3.2, 3.6 and 4.8 m were simulated using COMSOL Multiphysics. The device is fabricated using post CMOS approach namely deposition of 3.78 m thickness of Al doped Zinc Oxide (AZO) thin film, photolithography and wet etching. S-parameter measurements shows the series resonance frequency occurred at 1.156 GHz, 1.098 GHz and 0.966 GHz for three different wavelength respectively. The influence of acoustic wavelength on resonance frequency, acoustic wave velocity and electromechanical coupling coefficient were discussed. The best transmission characteristic was observed by Resonator 3 due to highest coupling coefficient of 0.069% and lowest insertion loss of 40.5 dB. The range of extracted SAW velocity is between 4161 m/s to 4497 m/s. Hence, the measurement results are consistent with finite element simulation results with deviation less than 5% in terms of resonance frequency and acoustic wave velocity.